Evaluation of the level of achievement of students of the faculties of education in Andalusian history (Journal of the College of Basic Education, 2022)
In light of the scientific and practical developments, educational systems are trying in all their joints to keep pace with this development, so specialists in educational sciences tend to study everything related to the educational educational life in order to reach the ultimate goal, which is a good educational environment that helps the student to advance at his level of knowledge. (Anwar and Al-Safi, 2007: 7)